Study on pitting corrosion behaviour of graphene oxide reinforced metal matrix composites. (2021) - Narayanan, S.; sozhamannan, G.G.; Hemalatha, K.; Venkatachalapathy, V.S.K.
Abstract: In this present study, the corrosion behavior of nano graphene oxide reinforced Aluminum alloy metal matrix composites investigated using pitting corrosion methods. The Al/GO composites were fabricated by ultrasonic stir casting technique. The effects of weight fraction of nano graphene oxides on the corrosion behavior of LM 24 aluminium alloy composites were analyzed. The corroded surfaces morphological were evaluated using scanning electron microscope and hardness was examined by microhardness tester. The experimental results were revealed that the corrosion rate was decreased with increases of weight percentage nano particles in the matrix. The microhardness values were gradually increased with increases of weight fractions of reinforcements in the matrix.